Prasangka Buruk Menimbulkan Penurunan Tingkat Kepercayaan Mahasiswa Bimbingan Penyuluhan Islam Terhadap Diri Sendiri - Lubis, Juli Rismayana; Tiffani, Tamara Dilla; Ayyubi, Muhammad Dilla; Mardiyah, Ainul (IAINU Kebumen, 2025)
This study aims to analyze the influence of negative prejudice on the level of self-confidence of Islamic Guidance and Counseling (BPI) students and to identify steps to overcome this problem.This study uses a qualitative approach with an in-depth interview method with 5 BPI students in semester VI at the State Islamic University of North Sumatra. The data were analyzed using thematic analysis to identify emerging patterns and themes. The results of the study showed that negative prejudices had a significant impact on reducing the self-confidence of BPI Danmpak students, which were identified as: (1) decreasing academic and non-academic participation, (2) decreasing academic achievement, (3) increasing stress and anxiety, and (4) difficulty building social relationships. Prejudice is a dominant factor in reducing the self-confidence of BPI students, which manifests itself in various academic, social, and psychological obstacles. Efforts to improve communication, openness to differences, and social support are needed to overcome this problem.